91 Technology-delivered intimate partner violence perpetration and victimization: prevalence and associations among a nationally-representative sample of young men. (5th May 2020) - Singh, Vijay; Tolman, Richard; Walsh, Tova; Ngo, Quyen
Abstract : Statement of Purpose: Determine prevalence and associations of technology-delivered intimate partner violence (IPV) among a nationally-representative sample of young men, using IPV groups of perpetration only, both perpetration and victimization, and victimization only. Methods/Approach: 1, 052 men age 18–35 years in nationally-representative sample completed surveys in September 2014. Validated measures examined demographics, health service use, mental health and substance use, and technology-delivered IPV (insulted partner, sent threatening messages, asked partner where they were at, checked partner's phone without permission, accessed partner's account without permission) perpetration and victimization. We conducted survey-weighted descriptive statistics and multinomial logistic regression. Results: Among men (mean age 26.5, 42.4% non-White), prevalence of technology-delivered IPV perpetration only was 4.1%, both perpetration and victimization was 25.6%, and victimization only was 8.0%. Technology-delivered IPV perpetration only was associated with prescription pain medication non-medical use (AOR 2.67, 95% CI 1.40–5.09); both perpetration and victimization was correlated with mental healthcare visits (AOR 1.89, 95% C.I. 1.18–3.05), alcohol misuse (AOR 1.11, 95% CI 1.05–1.17), and illicit drug use (AOR 1.48, 95% CI 1.00–2.19); and victimization only was associated with regular doctor for care (AOR 0.45, 95% C.I. 0.22–0.91), marijuana use (AOR 0.79, 95% C.I. 0.63–1.00), and prescription pain medication non-medical use (AOR 2.19, 95% CI 1.10–4.36). Conclusions: In the U.S. among young men, technology-delivered IPV was reported by 1 in 25 for perpetration only, 1 in 4 for both perpetration and victimization, and 1 in 12 for victimization only. Health service use, alcohol and substance use, and prescription opiate misuse correlates were similar for both perpetration and victimization, and victimization only, groups. Significance and Contributions to Injury and Violence Prevention Science: Healthcare providers in primary care and mental health can consider clinical assessment of young men for technology-delivered IPV perpetration, victimization, or both, along with associated mental health and substance use.